2020
DOI: 10.1038/s41436-019-0596-9
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer risks by gene, age, and gender in 6350 carriers of pathogenic mismatch repair variants: findings from the Prospective Lynch Syndrome Database

Abstract: PMS2 cause Lynch syndrome and result in different but imprecisely known cancer risks. This study aimed to provide age and organspecific cancer risks according to gene and gender and to determine survival after cancer. Methods: We conducted an international, multicenter prospective observational study using independent test and validation cohorts of carriers of class 4 or class 5 variants. After validation the cohorts were merged providing 6350 participants and 51,646 followup years. Results: There were 1808 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
430
3
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 447 publications
(477 citation statements)
references
References 18 publications
16
430
3
7
Order By: Relevance
“…Among LS patients, the majority of those developing extraintestinal malignancies are MSH2 mutation carriers [10,11]. Recent studies have shown that LS patients may present different neoplastic formations according to age, gender and type of MMR defect [3,4]. Furthermore, a worse prognosis has emerged among the elderly [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among LS patients, the majority of those developing extraintestinal malignancies are MSH2 mutation carriers [10,11]. Recent studies have shown that LS patients may present different neoplastic formations according to age, gender and type of MMR defect [3,4]. Furthermore, a worse prognosis has emerged among the elderly [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 1 in 279 people carry mutations in DNA mismatch repair genes [2]. Patients with MMR gene mutations have a significantly increased risk for cancer [3,4]; indeed, LS is the most common inherited colorectal susceptibility syndrome, accounting for approximately 3% of newly diagnosed cases of colorectal cancer and 3% of cases of endometrial cancer [5]. Although the predominant malignancies are colorectal and endometrial cancer, a wide variety of malignancies is reported, with sites including ovary, upper urinary tract, stomach, small bowel, pancreas, biliary tract, skin, and brain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Variability in results may reflect different methods of ascertainment, cohort sizes, ethnicity, or other factors. In the large multicenter prospective investigation by Dominguez-Valentin et al [5], the cumulative risk of breast cancer to 75 years of age was 12-15%, similar across all four MMR genes and representing only a marginal increase vs. average population.…”
Section: Research Papermentioning
confidence: 94%
“…studies, recent prospective studies have arrived at somewhat lower age-specific risk estimates for cancers occurring in MMR variant carriers; moreover, penetrance and expression patterns greatly depend on the MMR gene involved [5]. Among individual MMR genes, pathogenic variants in MLH1 and MSH2 have the highest and PMS2 the lowest penetrance, and MSH6 variants underlie a sex-limited trait with a high risk of gynecological cancers in females [5].…”
Section: Research Papermentioning
confidence: 99%
“…Those with defects involving the two main genes, MSH2 and MLH1, have a 75% probability of developing one or more of the cancers before they reach old age. 45 In 2017, the National Institute for Health and Care Excellence (NICE) announced that all colorectal cancers should be checked for evidence of mismatch repair deficiency in order to help identify families with LS. They were impressed by the clear evidence of benefit.…”
Section: Cancermentioning
confidence: 99%